Nanotechnology in the Treatment of Diabetic Complications: A Comprehensive Narrative Review - Yujing He; Abdulrahman Al-Mureish; Na Wu (Journal of Diabetes Research)
In today’s society, the prevention and treatment of diabetes mellitus and its subsequent complications have brought trouble to human beings. Complications caused by diabetes bring not only physical and mental pain to patients but also a heavy economic burden to families. And once diabetic complications occur, they are often irreversible and very difficult. At present, some studies suggest that nanotechnology can treat some diabetic complications. This paper reviews the application of nanotechnology in the repair of diabetic segmental bone injury, the healing of diabetic skin ulcers, the therapeutic effect, and improvement strategies and deficiencies of nanotechnology in diabetic complications.